"Combination Syndrome" in an Upper/Lower Implant Overdenture Patient: A Clinical Report. Issue 4 (August 2019) - Uram-Tuculescu, Sorin
Abstract : An upper/lower overdenture case, which presented with clinical entities commonly associated with the combination syndrome, is described. To the author's knowledge, this is the first documented case to illustrate such a particular association. The patient presented with an upper overdenture on 4 individual implants with attachments, without palatal coverage, opposing a lower bar overdenture on 4 implants, delivered more than 10 years before presentation. The patient complained about esthetics (poor display of upper teeth, excessive showing of lower teeth, and occlusal plane cant) and chewing. The anterior maxilla had severe bone loss, whereas the anterior mandible had a large amount of bone. Our retreatment included an upper overdenture with palatal coverage and a lower overdenture, both prostheses supported by individually attached implants. The article describes in detail the reasoning behind chosen retreatment, along with limitations and compromises.